2021
DOI: 10.3390/ma14195542
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Loading Angles and Implant Lengths on the Static and Fatigue Fractures of Dental Implants

Abstract: Mechanical properties play a key role in the failure of dental implants. Dental implants require fatigue life testing before clinical application, but this process takes a lot of time. This study investigated the effect of various loading angles and implant lengths on the static fracture and fatigue life of dental implants. Implants with lengths of 9 mm and 11 mm were prepared. Static fracture tests and dynamic fatigue life tests were performed under three loading angles (30°, 40°, and 50°), and the level arm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Sun et al 22 analyzed, by FEA, the influence of screw taper angle, observing that the 30° case had less wear and anti-loosening performance but lower life cycle than 180° one. He also evaluated the impact of loading angles and implant lengths 23 : the longer designs (11 vs 9 mm) presented better fatigue response whereas when the load angle increased, the fatigue life showed an exponential drop. In addition, the kind of abutment connection is also relevant as demonstrated by On et al 24 and by Gil et al 25 The thread type was investigated by Geramizadeh et al 26 discovering that the combination of microthreads in the upper area and V-shape in the rest of the body provided the best distribution of stress.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al 22 analyzed, by FEA, the influence of screw taper angle, observing that the 30° case had less wear and anti-loosening performance but lower life cycle than 180° one. He also evaluated the impact of loading angles and implant lengths 23 : the longer designs (11 vs 9 mm) presented better fatigue response whereas when the load angle increased, the fatigue life showed an exponential drop. In addition, the kind of abutment connection is also relevant as demonstrated by On et al 24 and by Gil et al 25 The thread type was investigated by Geramizadeh et al 26 discovering that the combination of microthreads in the upper area and V-shape in the rest of the body provided the best distribution of stress.…”
Section: Introductionmentioning
confidence: 99%
“… 3 6 The loading condition plays a vital role in the performance of dental implants. 7 , 8 A multicomponent dental implant assembly consists of an implant fixture, an abutment, and a connector screw. Generally, a torque is applied to the connector screw using a torque wrench to fix the abutment to the implant fixture adequately.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have reported dental implant mechanical performance using only the static loading part of the ISO 14801 protocol. Several reasons were described that prevented the use of cyclic testing of the ISO 14801, including a large sample size, more extended testing periods, and increased cost [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%